Analisis Faktor Risiko Kejadian Anemia pada Remaja Putri: Literatur Review - Rahman, Rika Ariana; Fajar, Nur Alam (Jurnal Kesehatan Komunitas, 2024)
Anemia is an indicator of malnutrition that can affect a country's economic development. anemia is a global health problem in the world. The prevalence of anemia in 2019 globally is 29.9%, Southeast Asia is 41.9% and in Indonesia (ages 15-49 years) is 30.6%. There is an increase in the prevalence of anemia in adolescents; from 22.7% (Riskesdas 2013) increased to 32% in the 2018 Riskesdas survey. The purpose of this study was to determine various risk factors for anemia in young women in several countries. Research method with literature review, secondary data sources (google scholar, pubmed, Sciencedirect. Results: from the review of articles in this study, the prevalence of anemia ranged from 20% to 47.7%. Research in Utar Paradesh India was 20%, in Ethiopia was 29.4% and the highest in Pakistan (2019) of 47.9% consisting of mild anemia 47.7%, moderate anemia 51.7% and severe anemia 5.7%. In Jordan the prevalence of anemia is 4.9% in men, 19 .3% in non-pregnant women, and 27.4% in pregnant women. Conclusion: in this literature study it was found that the factors affecting anemia in female adolescents were higher in the late adolescent phase, those who lived in rural areas, parents' education, socioeconomic level low number of family members, menstrual disorders and low intake of nutrients (micronutrients).For this reason, increasing education-based health education in schools is effective in increasing knowledge, attitudes and behavior in preventing anemia yes ng can make a real contribution in overcoming priority public health problems.